2017
DOI: 10.1121/1.5006205
|View full text |Cite
|
Sign up to set email alerts
|

Biaxial mechanical properties of human vocal fold cover under vocal fold elongation

Abstract: Mechanical properties of the human vocal fold cover layer were experimentally investigated in uniaxial and biaxial tensile tests. The results showed a coupling effect between the stress conditions along the anterior-posterior and transverse directions, with vocal fold elongation increasing vocal fold stiffness along both directions, thus allowing more efficient control of the fundamental frequency of voice through vocal fold elongation. This study also shows that vocal folds were nearly isotropic at resting co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 16 publications
2
18
0
Order By: Relevance
“…3 for both structural conditions. Similar to Zhang et al (2017), Fig. 3 shows that AP elongation not only increases the AP stiffness, but also significantly increases the transverse stiffness, particularly when elongation leads to recruitment of collagen fibers (for stretches above 1.1).…”
Section: Anisotropic Elastic Moduli Of Vocal Fold Cover and Ligamentsupporting
confidence: 53%
See 4 more Smart Citations
“…3 for both structural conditions. Similar to Zhang et al (2017), Fig. 3 shows that AP elongation not only increases the AP stiffness, but also significantly increases the transverse stiffness, particularly when elongation leads to recruitment of collagen fibers (for stretches above 1.1).…”
Section: Anisotropic Elastic Moduli Of Vocal Fold Cover and Ligamentsupporting
confidence: 53%
“…Compared with uniaxial tensile tests or indentation tests, biaxial tensile testing allows a better quantification of the anisotropic mechanical properties at different vocal fold longitudinal elongations and vibration amplitudes in the transverse plane, thus better approximating the realistic mechanical conditions that occur in human phonation. Indeed, the results from our recent biaxial tensile testing (Zhang et al, 2017) showed a strong mechanical coupling between the AP and transverse directions that was not observed in uniaxial tensile tests.…”
Section: Introductionmentioning
confidence: 80%
See 3 more Smart Citations